Expert-seeking activity framework: A proposal - Ghazali, Osman; Shiratuddin, Norshuhada; Sheik Osman, Wan Rozaini (2004)
Expert seeking is an activity in which one seeks expertise from someone else in order to solve certain problems. When one realizes he or she requires helps to accomplish tasks that need new skills and knowledge, the process involves many elements including formulating goals and strategies, identifying and selecting expert databases, and expert-seeking systems. By incorporating these elements, we proposed an expert-seeking activity framework, which can be guidance for researchers to better understand the activities of expert seeking.